Effects of glutamine, glutamate, and aspartate on intestinal barrier integrity and amino acid pool of the small intestine in piglets with normal or low energy diet - Deng, Yuankun; Cheng, Hao; Li, Junyao; Han, Hui; Qi, Ming; Wang, Nan; Tan, Bi'e; Li, Jianjun; Wang, Jing (Frontiers in Veterinary Science, 2023)
Aspartate (asp), glutamate (glu), and glutamine (gln) are the major energy fuels for the small intestine, and it had been indicated in our previous study that the mix of these three amino acid supplementations could maintain intestinal energy homeostasis. This study aimed to further investigate whether the treatment of gln, glu, and asp in low energy diet affects the intestinal barrier integrity and amino acid pool in weaning piglets. A total of 198 weaned piglets were assigned to 3 treatments: control (basal diet + 1.59% L-Ala); T1 (basal diet + 1% L-Gln + 0.5% L-Glu + 0.1% L-Asp); and T2 (low energy diet + 1% L-Gln + 0.5% L-Glu + 0.1% L-Asp). The blood, jejunum, and ileum were obtained on day 5 or on day 21 post-weaning, respectively. Our results showed that T1 and T2 treatments increased the abundances of occludin, claudin-1, and claudin-3 in the small intestine while decreasing the serum diamine oxidase (DAO) and D-lactate levels in weaning piglets. Meanwhile, T1 and T2 treatments significantly increased the positive rate of proliferating cell nuclear antigen (PCNA) of the small intestine, promoting intestinal cell proliferation. We also found that supplementation with glu, gln, and asp improved the serum amino acid pool and promoted ileal amino acid transporter gene expression of slc3a2, slc6a14, and slc7a11 in weaned piglets. Additionally, on day 21 post-weaning, T1 and T2 treatments stimulated the phosphorylation of the mTOR-S6K1-4EBP1 signaling pathway in the small intestine, which may implicate the enhanced protein synthesis rate. In summary, dietary supplementation of gln, glu, and asp was beneficial to the intestinal barrier function and amino acid pool regulation, while the benefits of gln, glu, and asp treatment might be diminished by the low-energy diet. The results demonstrated that the supplementation of gln, glu, and asp under low energy levels was preferentially supplied as the energy fuel to restore the gut barrier function in piglets on day 5 post-weaning. With the increase in age and intestinal maturation (on day 21 post-weaning), gln, glu, and asp supplementation could also show an effect on the regulation of the amino acid pool and protein synthesis.